The benefits of propofol on cancer treatment: Decipher its modulation code to immunocytes - Gu, Long; Pan, Xueqi; Wang, Chongcheng; Wang, Lei (Frontiers in Pharmacology, 2022)
Anesthetics are essential for cancer surgery, but accumulated research has proved that some anesthetics promote the occurrence of certain cancers, leading to adverse effects on the lives of patients. Although the anesthetic technology is mature, there isn’t a golden drug selection standard for surgical cancer treatment. To afford the responsibility of human health, a more specific regimen for cancer resection is indeed necessary. Immunosuppression in oncologic surgery has an adverse influence on the outcomes of patients. The choice of anesthetic strategies influences perioperative immunity. Among the anesthetics, propofol has shown positive effects on immunity. Apart from that, propofol’s anticancer effect is generally reported, which makes it more significant in oncologic surgery. However, the immunoregulative function of propofol isn’t reorganized well. Herein, we summarized the impact of propofol on different immunocytes, proposed its potential mechanism for the positive effect on cancer immunity, and offered a conceivable hypothesis on its regulation to postoperative inflammation. we concluded that the priority of propofol is high in oncologic surgery and propofol may be a promising immunomodulatory drug for tumor therapy.